Fortune Tiger on target: interface design, user experience, and online gambling addiction - Gomes Lourenço, Guilherme; Amorim , Patricia (InfoDesign, 2025)
This article investigates, within the scope of information design, how interface and user experience design elements are employed in the Fortune Tiger app, popularly known in Brazil as “Jogo do Tigrinho”. Through an analytical description of the game’s screens, based on notions of the cognitive triangle and emotional design, we identify visual and interactive resources designed to stimulate users to remain in a continuous cycle of repeated betting, contributing to the development and maintenance of gambling addiction.